Social Protection in South Africa During COVID-19: Exploring the Recommendation by UN Women to 'Put Cash in Women's Hands' in Response to the Pandemic - Vumazonke, Bulelani Janet (Department of Political Studies, 2025)
The outbreak of the COVID-19 pandemic has exposed and exacerbated pre-existing gender disparities worldwide. Countries expanded their social protection measures in response to the socio-economic implications of the health crisis. This study explores the South African government's social protection policies, and their impact on gender inequality during the pandemic, particularly in relation to social reproduction work and labour market dynamics. It investigates the expansion of social protection programmes, with attention to the Special COVID-19 Social Relief of Distress (SRD) Grant, a temporary cash transfer programme for working-age individuals with no source of income. In the labour market, it examines the implementation of the COVID-19 Temporary Employer-Employee Relief Scheme (TERS), a subsidy provided to companies by the government. The research extensively reviews existing literature, South African legislation, and particularly utilises the policy recommendation by UN Women to put cash in women's hands, as a strategy to mitigate the gender inequalities associated with the pandemic. By critically evaluating the government's strategies, the study contributes to illuminating the gendered impacts of COVID-19 in South Africa. A key finding of the mini-dissertation was that the government's social protection measures did not adequately address pre-existing gender disparities, and instead favoured men more than women. The study emphasises the necessity for a comprehensive and inclusive approach to social protection, that aims to address gender inequality and values care work. It proposes the introduction of a permanent grant targeted at women caregivers—a starting point to acknowledge the value of the social reproduction work they are accountable for